DETERMINAN PERILAKU KONSUMEN MUSLIM DALAM BELANJA ONLINE MENURUT PRESPEKTIF EKONOMI ISLAM (Studi Kasus Selama Pandemi Covid-19 Di Kota Surabaya) - pratiwi, dinda nurvianti; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2021)
The outbreak of a virus called covid-19, which first appeared in December 2019, shocked the world because of its very rapid spread. In Indonesia, the disease outbreak first appeared in March 2020, with 11,192 positive cases. With a high enough case, the government is trying to suppress the spread of the virus by making a PSBB policy, which has an impact on behavior change in society, one of which is economic activity. During the pandemic Covid-19, people tended to shop online as a safe solution. This study aims to determine the influence of cultural factors, social factors, personal factors, and psychological factors on consumer behavior in online shopping during the pandemic Covid-19. This type of research is quantitative with explanatory method with a review according to the perspective of Islamic economics. The data analysis technique used is partial test (t), simultaneous test (F) and the coefficient of determination (R2). The results of this study indicate that cultural factors, social factors, psychological factors influence consumer behavior in online shopping during the pandemic Covid-19, while personal factors have no influence on consumer behavior in online shopping during the pandemic Covid-19